Natural resource economics : theory and application in India - Kerr, J. M.; Marothia, Dinesh K.; Singh, Katar; Ramasamy, C.; Bentley, William R. (New Delhi : Oxford & IBH Pub. Co., 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Natural resources -- India; Environmental policy -- India